Serological survey on Hepatitis E virus in Namibian dogs, cats, horses, and donkeys - Molini, Umberto; Franzo, Giovanni; de Villiers, Lourens; van Zyl, Leandra; de Villiers, Mari; Khaiseb, Siegfried; Busch, Frank; Knauf, Sascha; Dietze, Klaas; Eiden, Martin (Frontiers in Veterinary Science, 2024)
The present study investigated the seropositivity rate of Hepatitis E virus (HEV) in domestic and working animals in Namibia, which included dogs, cats, horses, and donkeys. HEV poses a growing threat as a significant cause of human hepatitis globally and has several genotypes of varying zoonotic potential. As epidemiological data on the seroprevalence of HEV in Namibia is scarce, a serosurvey was conducted on archived serum samples of 374 dogs, 238 cats, 98 horses, and 60 donkeys collected between 2018 and 2022 from different regions, to assess the potential of these animals as sources of HEV infection. The findings revealed that 10.43% (n = 39/374) canine and 5.88% (n = 14/238) feline samples tested positive for HEV antibodies, whereas no seropositivity was detected in horses and donkeys. The study further examined the risk factors associated with HEV seropositivity, including animal sex, age, and geographical region, and noted a higher prevalence in dogs living in areas with intensive pig farming. Although there is no direct evidence indicating that these animals served as major reservoirs for HEV transmission to humans, the study underscores the importance of preventive measures to minimize contact exposure with pets considering the potential zoonotic risk, especially for susceptible risk groups. Further research is needed to explore the zoonotic potential of domestic animals and the epidemiological links between animal and human HEV transmissions in Namibia.